The influence of current ratio, debt to equity ratio, and return on assets on dividend payout ratio - Shabrina, Widya; Hadian, Niki (International Journal of Financial, Accounting, and Management, 2021)
Purpose: This study aimed to determine whether the current ratio, debt to equity ratio, and return on assets affected the dividend payout ratio of mining companies listed on the Indonesia Stock Exchange for the 2016-2018 period. Research Methodology: The research method used in this study was an explanatory method. The sampling technique used in this study was non-probability sampling with a purposive sampling technique so that the total sample size was 34 mining companies listed on the Indonesia Stock Exchange for the period 2016-2018. The analysis method used in this research was panel data regression analysis using Eviews 9. Results: The results showed that the current ratio, debt to equity ratio, and return on assets affected the dividend payout ratio. In addition, the research results also showed that the magnitude of the influence of the current ratio, debt to equity ratio, and return on assets in contributing to the dividend payout ratio was 51.5%. Limitations: The study was limited to only a few factors, namely the current ratio, debt to equity ratio, and return on assets to the dividend payout ratio. Contribution: This research is expected to be of benefit to the company in determining the policy of dividend distribution from several financial performance factors including current ratio, debt to equity ratio, and return on assets.